An Ex Ante View of Household Portfolio Choice: The Role of Expected Capital Gains - Ortmeyer, David L.; Peek, Joe (The Review of Economics and Statistics, 1986)
This paper highlights an issue not previously addressed in portfolio balance modelling: the impact of assetspecific expected capital gains on the composition of the household wealth portfolio. We extend the Brainard-Tobin portfolio choice model to incorporate the distinction between expected and unexpected capital gains and estimate two versions of the model. While our specification is more appealing on a theoretical basis, we were unable to distinguish clearly between the ex ante and ex post models given currently available data.